Diversity ‘Phyllophyte’ in Institutions of Higher Learning - Ndlovu, Dr Majaha (The journal of contemporary issues in business and government, 2022)
An exciting debate about diversity management, a subject of increasing interest over the last four decades in the business context, is even more relevant to institutions of higher education where diversity is present both in the supplier and customer side. The paper argues that the instrumental rather than normative argument that is presented in it will be based on the business case for diversity. Ordinarily the business case approach sees as a business opportunity and a means but not an end to attaining competitive edge making it possible to build creativeinstitutions (Cox & Blake, 1991; Pitts & Jarry, 2007).The paper further interrogates in nature-exploring diversity Management practices as embraced by institutions of higher learning, with special attention paid to Botswana context. The investigation employed dedicated focus group interviews, in-depth interviews and study of existing literature on diversity management. The adoption of triangulation meant that weaknesses and strength of each method offset the other solidifying the study findings. The paper also highlights the existing status quo in terms of diversity management in institutional contexts and further consolidates existing knowledge on diversity cultures across and within institutions. It further opens up an open -minded approach to dealing with unrelated and related aspects of work socially, economically, religiously and otherwise. The paper has just been written just when the COVID 19 pandemic effects and debates are ongoing. The findings of this paper have significant practical and research implication for scholars, academics, practitioners, policy makers and general populace. Given the fact that as individuals we construe meanings based on our values and beliefs the creation of an organizational culture which values diversity may rely on not only a shift in attitudes but an examination of underlying values.